PERAN SOSIAL MEDIA MARKETING DALAM MENINGKATKAN MARKETING PERFORMANCE MELALUI PEMANFAATAN DIGITAL MARKETING CAPABILITIES PADA PERUSAHAAN KONSTRUKSI DI PROPINSI JAWA TENGAH - Tobing, Wesly Tumbur ML; Santoso, Lukman (Universitas Sains dan Teknologi Komputer, 2024)
The aim of this research is to examine the role of social media marketing in creating a significant relationship between digital marketing capabilities and marketing performance in construction companies on the island of Java. The research method was carried out quantitatively by collecting data by distributing questionnaires via electronic forms and printed formats which were delivered directly to respondents where the respondents were directors who worked for contractor companies in Central Java province. The sampling technique was carried out purposively based on the criteria of directors who had worked for a minimum of five years at contractor companies in Central Java province. Based on these criteria, there are 225 company directors who have met these criteria. The data was analyzed using AMOS 22 statistical software. The research results showed that digital marketing capabilities had a positive and significant effect on social media marketing. Digital marketing capabilities do not have a positive and significant effect on marketing performance, and social media marketing has a positive and significant effect on marketing performance.